2012
DOI: 10.1038/onc.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

CBL enhances breast tumor formation by inhibiting tumor suppressive activity of TGF-β signaling

Abstract: Casitas B-lineage lymphoma (CBL) protein family functions as multifunctional adaptor proteins and E3 ubiquitin ligases that are implicated as regulators of signaling in various cell types. Recent discovery revealed mutations of proto-oncogenic CBL in the linker region and RING finger domain in human acute myeloid neoplasm, and these transforming mutations induced carcinogenesis. However, the adaptor function of CBL mediated signaling pathway during tumorigenesis has not been well characterized. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 31 publications
(32 reference statements)
0
32
0
Order By: Relevance
“…Additionally, YC-1 induced EGFR degradation in a proteasome-dependent manner, and the depletion of c-Cbl attenuated YC-1-induced EGFR inhibition (data not shown), which indicated that YC-1 also mediated c-Cbl to promote EGFR degradation. c-Cbl functions as a proto-oncogene, which is related to tumourigenesis in breast cancer (Kang et al, 2012). The YC-1-induced c-Cbl suppression may also contribute to antitumour activity in MDA-MB-468 cells.…”
Section: Figurementioning
confidence: 99%
“…Additionally, YC-1 induced EGFR degradation in a proteasome-dependent manner, and the depletion of c-Cbl attenuated YC-1-induced EGFR inhibition (data not shown), which indicated that YC-1 also mediated c-Cbl to promote EGFR degradation. c-Cbl functions as a proto-oncogene, which is related to tumourigenesis in breast cancer (Kang et al, 2012). The YC-1-induced c-Cbl suppression may also contribute to antitumour activity in MDA-MB-468 cells.…”
Section: Figurementioning
confidence: 99%
“…This occurs through direct binding with Smad3 and not Smad2 in a C-terminal phosphorylation-dependent manner, preventing Smad3 from forming a complex with Smad4. 65 Recently, the transcriptional co-regulator SKI was found to promote linker phosphorylation of Smad3 and TGFβ-induced oncogenesis in melanoma cells. 66 In invasive breast cancer tissue samples, increased cytoplasmic SKI expression is inversely associated with tumor size, stage and lymph node status and positively associated with longer disease-free survival.…”
Section: Additional Mechanisms Of Smad3 Regulationmentioning
confidence: 99%
“…SNU16 cell lines stably expressing control or KIAA1324 shRNA were generated as described previously (25). To establish MKN28 and AGS cell lines expressing KIAA1324 in a doxycycline-dependent manner (tet-on), the human KIAA1324 gene was cloned into pCMV-3HA vector (Clontech).…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%